Simulation, synthesis, and analysis of strontium-doped ZnO nanostructures for optoelectronics and energy-harvesting devices - Anjum, Muhammad Shafiq; Ashraf, Muhammad Waseem; Tayyaba, Shahzadi; Imran, Muhammad (Frontiers in Materials, 2023)
The demand for clean and sustainable alternative energy resources is linearly increasing day by day due to the prevailing electricity crisis. Small-scale energy harvesting is considered a sustainable way to generate clean energy. Advanced energy solar cells, mainly dye-sensitized solar cells use solar energy and convert it into electrical energy. Similarly, MEMS-based piezoelectric materials are used to convert mechanical energy into electrical energy. For these applications, zinc oxide is considered one of the most suitable materials with high conductive, tunable band gap, and piezoelectric properties. However, altering these properties can be carried out by the addition of metal and other materials. Various research work has been carried out to study the addition of conductive metal as a dopant to alter the properties of zinc oxide. In this study, Strontium has been doped in ZnO to form a nanostructure for application in DSSC and microelectromechanical systems (MEMS) energy harvesters. Analysis has been conducted using the simulation and fabrication method. The results show that the doping and the pore size of the substrate (Anodic Aluminum oxide membrane) largely affect the output voltage and current. The difference between the simulated and experimental results was less than 1%, which shows the accuracy of the simulation. Tuning of the band gap can be observed by the addition of Sr in the ZnO nanostructure. For microelectromechanical systems energy harvesters, Sr-doped ZnO nanostructures deposited on anodic aluminum oxide show 7.10 mV of voltage and 1.11 uA of current output. The addition of Sr doping in ZnO shows the improvement in the generated current and voltage for the energy harvester and the improvement in overall power conversion efficiency for dye-sensitized solar cells. MEMS-based energy harvesting devices and low-cost advanced solar cells are promising to improve the efficiency of energy generation at a small scale.